A c.3037G>A mutation in FBN1 gene causing Marfan syndrome with an atypically severe phenotype. - Callea, Michele; Willoughby, Colin Eric; Camarata-Scalisi, Francisco; Giovannoni, Isabella; Vinciguerra, Agatino; Yavuz, Izzet; Di Stazio, Mariateresa; Di Iorio, Enzo; Clarich, Gabriella; Benettoni, Alessandra; Galeotti, Angela; Bellacchio, Emanuele (Investigación Clínica, 2017)
Ver Resumen PDF.